(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Malaysian Armed Forces divided into three services, namely the Malaysian Army, Royal Malaysian Navy and the Royal Malaysian Air Force. Royal Malay Regiment (RMR) is the main infantry unit in the Malaysian Army. RMR are highly emphasized the organization commitment by educate officers and other ranks such as training, workplace facilities and adequate work motivation. This is because personnel will quickly decide to quit early, leave their job, drug abuse and bullying other personnel and etc. The objective for this study is study determinesthe relationship between the leadership style and recognition with organization commitment amongRMR personnel. The quantitative research method by distributing questionnaires was used to obtain feedback on 120 respondents who were sampled for this study. This study uses a questionnaire that contains several questions on leadership style, recognition and organization commitment. The data were analysed using Statistical Package for Social Science (SPSS) version 25 and Smart Partial Least Squares (PLS) version 3.2.8. The findings showed a significant relationship between leadership style and recognition with organization commitmentamong RMR.This study found that the leadership style and recognition among RMR were positive related to the organization commitment, meaning that the personnel of RMR feel more loyal to their leader. The RMR may consider additional factors influencing RMR instructors to commit to RMR programmes in future work.This research is also a valuable resource for leader who wish to enhance their training. By helping them to avoid the longstanding problem of leader discontent in the country, it can be employed to help ensure that they continue to enjoy their careers.